Duodenal lesions management - Lastra Santiago, Maria A.; Muñoz Delgado, Gustavo E. (International Surgery Journal, 2023)
Penetrating injuries are more typical overall, and traumatic damage to the duodenum only happens in 3 to 5% of individuals with abdominal injury. The majority of blunt injuries in the US are brought on by auto accidents. Lesions are evenly dispersed across the other sections of the duodenum, with the second segment being more frequently afflicted. Duodenal damage symptoms are non-specific and could be less noticeable after retroperitoneal surgery. Computed tomography (CT) is used to evaluate the duodenum in the diagnosis of duodenal injury in hemodynamically stable patients. CT findings related to this evaluation include duodenal thickening, periduodenal fluid, extraluminal air, and accumulation of heterogeneous fluid (clot) close to the site of injury. According to the mechanism and severity of the damage, the care of duodenal lesions should be cautious in patients with grade I or grade II closed duodenal hematoma who are hemodynamically stable. When duodenal lesions need to be repaired, surgery is necessary. With death rates of about 15%, duodenal injury complications include intra-abdominal abscess, duodenal fistula, and post-traumatic pancreatitis.